Tumor and peritumoral adipose tissue crosstalk: De-differentiated adipocytes influence spread of colon carcinoma cells. (February 2023) - Conti, G.; Calderan, L.; Quintero Sierra, L.A.; Conti, A.; Ossanna, R.; Boschi, F.; Marzola, P.; Ferrarini, F.; Governa, M.; Lievens, P.M.-J.; Sbarbati, A.
Abstract: Colorectal cancer is the second leading cause of cancer and often has a fatal course. There are many studies in the literature that have described a close functional relationship between the tumor mass and surrounding tissue, or tumor stroma, which is affected by the continuous metabolic exchange that occurs at the interface between tumor and tissues in contact with it. There is much evidence that the presence of adipose tissue in stroma plays a fundamental role in modulating the tumor microenvironment and promote tumor development, growth, and angiogenesis due to its endocrine characteristics. In this analysis, we have studied the alterations of adipose tissue surrounding colorectal tumors with MRI and optical imaging in vivo techniques to monitor tumor progression and also performed histological and molecular analysis. We detected differences in the principal adipose markers expressed by adipocytes residing around the rectal colon and observed that peritumoral adipose tissue is exposed to a mesenchymal transition process that leads to the acquisition of a less differentiated phenotype of adipocyte that represents the main cellular type present in tumor stroma. The mesenchymal transition correlated with the acquisition of more aggressive tumor phenotype and could represent a valid target for tumor therapy. Highlights: Adipose tissue surrounding tumor could influence the tumor growth and dissemination. Adipose tissue surrounding tumors is characterized by peculiar morphological features. Multilocular adipocytes surrounding tumors don't express the typical markers of white and brown fat. Adipose tissue surrounding tumor could represent a new therapeutic target.